The comparison of microdose flare up and flexible antagonist protocols in poor responders undergoing IVF treatment: A prospective randomized controlled trial - Özdoğan, Serdinç; Özdeğirmenci, Özlem; Dilbaz, Serdar; Demir, Berfu; Çınar, Özgür; Dilbaz, Berna; Göktolga, Ümit (Journal of Surgery and Medicine, 2019)
Aim: Ovarian reserve is one of the most important prognostic factors to predict probability of pregnancy in in vitro fertilization (IVF) cycles. Poor ovarian response is associated with high cycle cancellation rate and diminished pregnancy rates. Therefore, the management of women who demonstrate an inadequate response to controlled ovarian hyperstimulation (COH) are a challenge to treat with IVF. Methods: A hundred consecutive infertile women, defined as poor responder, were recruited to this study. It was conducted at the assisted reproductive technology (ART) unit of the Ankara Etlik Zubeyde Hanim Women's Health Teaching and Research Hospital during the period September 2009 to September 2011. All patients in Group 1(n=50) were treated by using flexible gonadotropin releasing hormone (GNRH) antagonist protocol and in Group 2 (n=50) were treated by using GnRH microdose flare-up protocol. Exogenous gonadotropin (Gonal F, Serono, Istanbul, Turkey) was initiated on the second day of menstruation in all patients in Group 1(n=50) and GnRH antagonist (0.25 mg, Cetrotide; Serono, Geneva, Switzerland) was started when the leading follicle reached 12 mm in mean diameter and were continued until the day of hCG administration. Results: Total dosage of gonadotropins was significantly higher in group 2 (2625 IU in group 1 vs 4050 IU in group 2; p<0.001). The pregnancy rate was higher in group 2 but not statistically significant (25.7% in group 1 vs 33.3% in group 2; p=0.501). Conclusion: There is no consensus on the best standard treatment option for assisted reproductive technology (ART) cycles of poor responders. GnRH antagonist and microdose flare-up protocols seem to have similar outcomes in poor responder patients in intracytoplasmic sperm injection (ICSI) cycles except consumption of gonadotropins. Further prospective randomized trials with large sample size are needed to assess the efficacy of the two protocols in the poor responders.